Vertical oviposition activity of mosquitoes in the Atlantic Forest of Brazil with emphasis on the sylvan vector, Haemagogus leucocelaenus (Diptera: Culicidae). Issue 1 (June 2016) - Alencar, Jeronimo; de Mello, Cecilia Ferreira; Gil‐Santana, Hélcio R.; Guimarães, Anthony Érico; de Almeida, Sergio Antonio Silva; Gleiser, Raquel M.
ABSTRACT: This study aimed to assess the vertical patterns of oviposition and temporal changes in the distribution of mosquito species in an area of the Atlantic Forest in Rio de Janeiro State, Brazil, and in particular, the behavior and oviposition of potential yellow fever virus vectors. Mosquito samples were collected from the Ecological Reserve Guapiaçu (REGUA, Brazil), which includes a somewhat disturbed forest, with a large diversity of plants and animals. In all, 5, 458 specimens (ten species from seven genera) were collected. Haemagogus leucocelaenus was the most frequently captured species, representing 73% of the specimens collected. Species richness and diversity were the highest in the samples collected from the ground‐level ovitraps and decreased with height. Species composition also differed significantly among heights. The largest species differences were detected between ovitraps set at the ground level and those set at 7 m and 9 m; Hg. leucocelaenus, Limatus durhamii, and Limatus paraensis contributed most to these differences. Sampling month and climatic variables had significant effects on species richness and diversity. Species diversity and richness decreased with height, suggesting that the conditions for mosquito breeding are more favorable closer to the ground. Species composition also showed vertical differences.